Mechanisms responsible for beneficial and adverse effects of rosiglitazone in a rat model of acute cardiac ischaemia-reperfusion - Siripong Palee (2018)
New Findings: • What is the central question of this study? Controversy exists regarding the beneficial and adverse effects of rosiglitazone. We sought to determine the effects of rosiglitazone in the heart during ischaemia-reperfusion injury. • What is the main finding and what is its importance? We demonstrated that rosiglitazone simultaneously exerted both beneficial and adverse effects on the heart during ischaemia-reperfusion. These findings provided new mechanistic insights into the effects of this drug, and elucidate the possibility of its undesirable effects in patients taking this drug. Despite debate regarding its cardioprotective and pro-arrhythmic effects, the precise mechanisms of action of rosiglitazone on the heart are still unclear. We determined the mechanistic effects of rosiglitazone on cardiac function, arrhythmias and infarct size during cardiac ischaemia-reperfusion. Twenty-six rats were used. In each rat, either rosiglitazone or saline solution was administered intravenously prior to a 30 min left anterior descending coronary artery ligation and a 120 min reperfusion. Cardiac function, infarct size, myocardial levels of connexin43, Bax/Bcl-2, cytochrome c, caspase-3, caspase-8, Akt, tumour necrosis factor-α and interleukin-4 and cardiac mitochondrial function were determined. Isolated cardiomyocytes were used for studying intracellular calcium. Rosiglitazone did not alter cardiac function during the ischaemia-reperfusion periods, but increased the arrhythmia score and mortality rate, decreased the time to onset of ventricular fibrillation and prolonged the Ca 2+ decay rate, in comparison to the saline-injected group (P < 0.05). However, the infarct size in the rosiglitazone-injected group was reduced (P < 0.05). Rosiglitazone decreased the levels of connexin43 phosphorylation, active caspase-8 and tumour necrosis factor-α, but increased the level of procaspase-3. However, levels of Bax/Bcl-2, cytochrome c, Akt and interleukin-4 and the cardiac mitochondrial function were not different between the two groups. Rosiglitazone simultaneously exerted both beneficial and adverse cardiac effects in the heart exposed to ischaemia-reperfusion. Although it decreased the infarct size via the extrinsic anti-apoptotic pathway and anti-inflammatory effects, rosiglitazone facilitated a fatal arrhythmia by decreasing connexin43 phosphorylation and prolonging the Ca 2+ decay rate in ischaemia-reperfusion. The higher mortality rate in the rosiglitazone-injected group suggests that its undesirable effect was more pronounced than its benefit on infarct size reduction. © 2013 The Authors. Experimental Physiology © 2013 The Physiological Society.